1954
DOI: 10.1002/cber.19540870102
|View full text |Cite
|
Sign up to set email alerts
|

Studien in der Vitamin D‐Reihe: Umlagerung des Vitamins D2 zu einem iso‐Tachysterin und Partialsynthese eines iso‐Vitamins D2)

Abstract: Vitamin D, konnte durch Behandlung mit Bortrifluorid-atherat unter Verschiebung des gesamten Trien-Systems in ein neues Isomeres umgelagert werden, daa als im-Tachysterin bexeichnet wird.Weiterhin konnte ein ieo-Vitamin D, partialsynthetiech gewonnen werden, wobei der BUS Vitamin D, durch Abbau erheltene C,.-Aldehyd Verwendung fand.Durch Oxydation von iao-Tachysterin sowie durch Umlagerung und Oxydation von bo-Vitamin D, wurden schliealich identische Trien-ketone erhalten. Die Konfiguration der boiden neuen Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1954
1954
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Further, autoantibodies to TBM were found in acid eluates of these kidneys. These experiments confirm that the transfer of tubulointerstitial disease is dependent on the transfer of sufficient amounts of donor autoantibodies to TBM; moreover, serums with or without autoantibody to GBM produced on transfer the identical tubulointerstitial nephritis (9).…”
supporting
confidence: 67%
“…Further, autoantibodies to TBM were found in acid eluates of these kidneys. These experiments confirm that the transfer of tubulointerstitial disease is dependent on the transfer of sufficient amounts of donor autoantibodies to TBM; moreover, serums with or without autoantibody to GBM produced on transfer the identical tubulointerstitial nephritis (9).…”
supporting
confidence: 67%
“…Aldersley and Burkhardt [74] set out independently of Dimroth on the same synthetic route at the same time. Sixteen years later, Inhoffen, Brückner and Gründel [72] followed up Dimroth's basic concept, but this time no longer in exploratory fashion, with exchangeable model compounds, but on the far more challenging exhibition ground, with use of the so-called C 20 -degradation aldehyde from vitamin D 3 and 4-acetoxycyclohexanone as condensation components (Scheme 14). The Braunschweig chemists would have failed, just like all their predecessors, in the installation of the exocyclic methylene group on the future ring A had they not had the good fortune of being able to apply the just published Wittig reaction for their purposes.…”
Section: Scheme 13mentioning
confidence: 98%
“…[28c] The first publication within a series of papers, with the understated title Studien in der Vitamin D-Reihe, [72] began with the announcement to carry on Göttingen's vitamin D tradition in nearby Braunschweig. The Göttingen tradition in this context, by the way, included not only Windaus's investigations into the irradiation products of ergosterol, but also the Synthetic Experiments in the Preparation of Anti-rickets Vitamins undertaken in Göttingen by Karl Dimroth shortly before the Second World War.…”
mentioning
confidence: 99%
“…However, there are only very limited reports regarding this process. It was reported that Vitamin D, pre-Vitamin D and tachysterol can be converted to isotachysterol in various acidic conditions such as HCl, BF 3 and H 3 PO 3 [22][23][24][25]. It was reported that 25-hydroxyvitamin D or 24,25-dihydroxyvitamin D could also be transformed into the corresponding isotachysterols by treatment with hydrochloric acid [26].…”
Section: Acid Induced Degradationmentioning
confidence: 99%